Esophyllas, a new genus of erigonine spiders from southern California (Araneae: Linyphiidae: Erigoninae) - Prentice, Thomas R.; Redak, Richard A. (Zootaxa, 2012)
We erect a new genus, Esophyllas n. gen., to place two litter dwelling species of erigonine spiders from southern Califor-nia the type species, E. vetteri n. sp. and E. synankylis n. sp. A detailed genus diagnosis is presented as well as compre-hensive morphological descriptions, artist illustrations, and SEM images for each species. We also provide data on habitataffinities, phenology, and distribution, including a distribution map figure. For tentative phylogenetic placement both spe-cies were scored for the characters in the data matrix of Miller & Hormiga (2004) and subsequently entered into the ex-panded matrix of Frick et al. (2010). The analysis places Esophyllas n. gen. within the “distal erigonines” as sister toScirites Bishop and Crosby in a polytomy with Tapinocyba Simon 1884 and Abacoproeces (L. Koch). Data from morpho-logical comparisons with taxa not included in the expanded matrix do not strongly support these relationships but insteadsuggest that Esophyllas n. gen. is more closely related to Phlattothrata parva (Kulczyn’ski 1926). However, in light ofthe extent of character divergence from the above genera we contend that the true sister group to Esophyllas n. gen. either has not yet been described or is among the vast number of phylogenetically untested taxa.